Receipt of cardiac screening does not influence 1-year post–cerebrovascular event mortality. Issue 3 (June 2018) - Sico, Jason J.; Baye, Fitsum; Myers, Laura J.; Concato, John; Ferguson, Jared; Cheng, Eric M.; Jadbabaie, Farid; Yu, Zhangsheng; Arling, Gregory; Zillich, Alan J.; Reeves, Mathew J.; Williams, Linda S.; et al.
Abstract : Background: American Heart Association/American Stroke Association expert consensus guidelines recommend consideration of cardiac stress testing to screen for occult coronary heart disease (CHD) among patients with ischemic stroke/TIA who have a high-risk Framingham Cardiac Risk Score (FCRS). Whether this guideline is being implemented in routine clinical practice, and the association of its implementation with mortality, is less clear. Methods: Study participants were Veterans with stroke/TIA (n = 11, 306) during fiscal year 2011 who presented to a VA Emergency Department or who were admitted. Patients were excluded (n = 6, 915) based on prior CHD/angina/chest pain history, receipt of cardiac stress testing within 18 months prior to cerebrovascular event, death within 90 days of discharge, discharge to hospice, transfer to a non-VA acute care facility, or missing/unknown race. FCRS ≥20% was classified as high risk for CHD. ICD-9 and Common Procedural Terminology codes were used to identify receipt of any cardiac stress testing. Results: Among 4, 391 eligible patients, 62.8% (n = 2, 759) had FCRS ≥20%. Cardiac stress testing was performed infrequently and in similar proportion among high-risk (4.5% [123/2, 759]) vs low/intermediate-risk (4.4% [72/1, 632]) patients (adjusted odds ratio [aOR] 0.77, 95% confidence interval [CI] 0.54–1.10). Receipt of stress testing was not associated with reduced 1-year mortality (aOR 0.59, CI 0.26–1.30). Conclusions: In this observational cohort study of patients with cerebrovascular disease, cardiac screening was relatively uncommon and was not associated with 1-year mortality. Additional work is needed to understand the utility of CHD screening among high-risk patients with cerebrovascular disease.